2022
DOI: 10.1038/s41598-021-04360-y
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of SARS-CoV-2 and PR8 H1N1 virus to cold atmospheric plasma activated media

Abstract: Cold Atmospheric Plasma (CAP) and Plasma Activated Media (PAM) are effective against bacteria, fungi, cancer cells, and viruses because they can deliver Reactive Oxygen and Nitrogen Species (RONS) on a living tissue with negligible damage on health cells. The antiviral activity of CAP against SARS-CoV-2 is being investigated, however, the same but of PAM has not been explored despite its potential. In the present study, the capability of Plasma Activated Media (PAM) to inactivate SARS-CoV-2 and PR8 H1N1 influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The calculations were performed using an online tool “Quest GraphTM IC 50 Calculator, AAT Bioquest, Inc.” by using eqn (3). 85,86 The measurements were normalized to the intensity of untreated HEWL amyloid fibrils (taken as 100%).…”
Section: Resultsmentioning
confidence: 99%
“…The calculations were performed using an online tool “Quest GraphTM IC 50 Calculator, AAT Bioquest, Inc.” by using eqn (3). 85,86 The measurements were normalized to the intensity of untreated HEWL amyloid fibrils (taken as 100%).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, gas-fed NTP, such as plasma jets, could present additional health risks, as the constant gas flow could blow microdroplets that carry viruses and other contaminating particles into the surrounding environment, thus further spreading its reach. Another strategy which uses NTP for disinfection is via generation of NTP-treated liquids, such as water. , In this modality, NTP is used to treat and enrich a liquid with RONS. This liquid is then applied to the surface to be disinfected.…”
Section: Discussionmentioning
confidence: 99%
“…Cortazar et al found that RONS induced by PAM delivers on a living tissue with negligible damage on healthy cells. In contrast, their PAM inactivated SARS-CoV-2 and PR8 H1N1 viruses effectively [ 48 ]. It was reported that the synergistic effect of H 2 O 2 , RONS and a low pH may induce cell death of infected cells.…”
Section: Discussionmentioning
confidence: 99%